Heat-Killed Tobacco Mosaic Virus Mitigates Plant Abiotic Stress Symptoms - Augustine, Sruthy Maria; Tzigos, Stavros; Snowdon, Rod; Justus Liebig University Giessen (My University, 2022)
Since the discovery of the tobacco mosaic virus in the 1890s, awareness has grown in regard to how viruses affect the environment. Viral infections are now known to cause various effects besides pathogenicity, with some viruses in fact having a beneficial impact on plants. Although research has focused on disease-causing viruses that can infect plants, many wild plants are also infected with non-pathogenic viral agents. Traditionally, abiotic, and biotic stresses have been studied as isolated stimuli that trigger signaling pathways within the plant. However, both biotic and abiotic stress can trigger complex molecular interactions within plants, which in turn drive interconnected response pathways. Here, we demonstrate that heat-killed tobacco mosaic virus (TMV) can increase abiotic stress tolerance in plants, an effect that could potentially be implemented in challenging growth environments. To our knowledge, this is the first report of plant abiotic stress tolerance following treatment with heat-killed viral particles.
Keywords: drought stress tolerance; heat killed virus; tobacco mosaic virus; ddc:630